Law Enforcement in The Handling of People Smuggling Crime in Indonesia - Herbin Marulak Siahaan (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2020)
People Smuggling is a rising phenomenon of Transnational Organized Crime. Indonesia has taken an important step to combat this phenomenon by ratifying the UN Protocol against Smuggling of Migrants which set of key obligations relating to People Smuggling. This normative legal research aims to identify and discuss the challenges to convert these obligations into practical outcomes. The research results show some practical challenges for the law enforcement agencies responsible for combating people smuggling which includes a number of issues that relate to the prosecutions of migrant smugglers and to the dismantling of smuggling networks. Therefore, it is necessary to have a model of law enforcement in handling a crime as complex as people smuggling by improving the legal substance, the legal structure as well as the community participation in regional perspectives.